A) 1/2
B) 1
C) 0
D) -1/2
Correct Answer: D
Solution :
\[\sin ({{\cot }^{-1}}(x+1))=\cos ({{\tan }^{-1}}x)\] \[\Rightarrow \]\[\cos (\pi /2-{{\cot }^{-1}})(x+1))=\cos ({{\tan }^{-1}}x)\] \[\Rightarrow \]\[\frac{\pi }{2}-{{\cot }^{-1}}(x+1)=2n\pi \pm {{\tan }^{-1}}x\] Put\[n=0\Rightarrow \pi /2-{{\cot }^{-1}}(x+1)=\pm {{\tan }^{-1}}x\] \[={{\tan }^{-1}}(\pm x)\] \[\Rightarrow \]\[\pi /2={{\tan }^{-1}}(\pm x)+{{\cot }^{-1}}(x+1)\] \[\Rightarrow \]\[x+1=\pm x\Rightarrow 2x+1=0\]\[x=-\frac{1}{2}\]You need to login to perform this action.
You will be redirected in
3 sec